The Explicit Instruction Model: An Effective Strategy to Improve Practical Achievement of Maritime Vocational School Students - Wegig Pratama (Bulletin of Science Education, 2024)
This study aims to improve the practical performance of Maritime Vocational High School students through the Explicit Instruction model, focusing on enhancing competencies in safety and basic navigation of shipping. The study used a Classroom Action Research (CAR) approach with the Kemmis and Taggart model, consisting of three cycles including planning, action implementation, observation, and reflection. The research subjects consisted of 25 students from class XI of the Nautical Ship Commerce major at SMK Poetra Samudra. Data were collected through observation sheets and practical assessments covering aspects of work preparation, work knowledge, and work skills, verified by maritime industry instructors. The results of the cycle evaluations showed a model effectiveness level of 88% (very good category), with significant improvements in competency scores from cycle I to cycle III, particularly in work skills (56.3% increase). Limited trials indicated that the implementation of the Explicit Instruction model had a positive impact on improving students' practical competencies, especially in procedural skills and safety procedures, with an average score increase to 3.6 (very good category). Teacher and student responses to the model were also in the very positive category, as reflected in increased engagement and discipline during practice sessions. Therefore, this learning model is deemed effective, systematic, and contextual for implementation in maritime vocational education to enhance technical competencies and professional work readiness.